Does diurnal variation affect the first trimester fetal aneuploidy screening test biochemical parameters of fetuses with normal nuchal translucency?. (2nd June 2016) - Karsli, Mehmet Fatih; Cakmak, Bulent; Seckin, Kerem Doga; Akkas Yilmaz, Elif; Akgul, Gurcan; Togrul, Cihan; Kucukozkan, Tuncay
Abstract: Objective : The purpose of this study was to investigate the effect of diurnal variation on biochemical results of first trimester aneuploidy screening test. Methods : A total of 2725 singleton pregnant female, who had normal fetal nuchal translucency (NT) thickness, were included in the study during this period. Individuals were divided into two groups according to the sampling time (morning group: 09:00–11:00 am and afternoon group: 02:00–04:00 pm). Hormonal parameters (free-beta human chorionic gonadotropin [free β-hCG] and pregnancy-associated plasma protein-A [PAPP-A] multiples of median [MoM] levels) of first trimester (11 +0 –13 +6 weeks) combined aneuploidy screening test were compared between morning and afternoon groups. Results : PAPP-A MoM levels were significantly lower in the afternoon group when compared to the morning group ( p  = 0.001), whereas free β-hCG MoM levels were similar in the both groups ( p  = 0.392). Rate of high risk for Down syndrome (Combine risk >1/300) and amniocentesis ratio were found higher in the afternoon group than morning group, but there were no difference between groups for the number of fetuses with Down syndrome. Conclusion : Receiving the venous blood sample for first trimester aneuploidy screening test in the afternoon causes low PAPP-A MoM levels.